ANALISIS PENERAPAN TRANSAKSI NON-TUNAI (CASHLESS) DALAM PENGELOLAAN KEUANGAN TOKO AL-ZAYTUN DITINJAU DARI HUKUM EKONOMI ISLAM - Nur Fadhilah; Irvan Iswandi; Ali Aminulloh (PT. Hasba Edukasi Mandiri, 2025)
This thesis examines the implementation of non-cash or cashless transactions in the financial management of the Al-Zaytun store and its review in Islamic economic law. The purpose of this study is to explain the flow of implementing non-cash transactions (cashless) at the Al-Zaytun store in financial management and to analyze its implementation according to Islamic economic law. This study uses a qualitative research method with a qualitative descriptive approach and a type of field research, using data collection methods, namely observation, interviews, and documentation. The primary data source in this study is the results of interviews obtained from agencies related to the implementation of non-cash transactions (cashless), while secondary data is obtained through shopping formats, letters of application for disbursement of funds, WhatsApp groups, journals and others related to the object of research. The results of the study concluded that, first, the implementation of non-cash transactions begins with the cashless implementer submitting a shopping request via WhatsApp, the dormitory savings then processes the request into a shopping format and the cashless implementer makes a transaction at the Al-Zaytun store. The transaction is declared complete with the signatures of 2 parties, namely the store and the cashless implementer, the dormitory savings processes the shopping format with the final result being a letter of request for disbursement of funds. The letter is submitted to the MPAP secretary. MPAP will submit the request to the chairman of the foundation for approval of the request. the request is approved and MPAP submits the request to Syaykh Al-Zaytun as the final ratifier. After being approved, MPAP requests funds from the BPR. BPR submits the amount of funds requested. Then the funds are distributed to the relevant units. Second, the implementation of non-cash transactions (cashless) in accordance with Islamic economic law reviewed from the aspects of the validity of the principles of Sharia economics, there is no element of fraud or gambling in buying and selling that is detrimental to one party.